DNA barcoding and taxonomic review of the barklouse genus Stenopsocus (Psocoptera: Stenopsocidae) from Taiwan - Liang, Feiyang; Dai, Yuting; Yue, Lu; Li, Fasheng; Liu, Xingyue (Zootaxa, 2015)
The barklouse genus Stenopsocus Hagen is the most diverse group of the family Stenopsocidae, with 139 described species recorded from China in a previous study. However, due to the considerably similar morphology, species identification in this genus is problematic. In the present study, we used DNA barcoding to delimit the six Stenopsocus species currently recorded in Taiwan. Our results show that S. aphidiformis, S. niger, S. tibialis, S. makii, and S. formosanus can be clearly distinguished based on COI sequences. Although genetic divergence between S. formosanus and S. externus was not detected, we tentatively consider that these two species are valid based on their remarkably different morphological features. Re-descriptions of these six valid species are provided. Stenopsocus niger is newly recorded from Taiwan, and S. formosanus newly recorded from Vietnam.